2010
DOI: 10.1063/1.3514100
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation in microfluidic beam resonators: Dependence on mode number

Abstract: Energy dissipation experienced by vibrating microcantilever beams immersed in fluid is strongly dependent on the mode of vibration, with quality factors typically increasing with mode number. Recently, we examined energy dissipation in a new class of cantilever device that embeds a microfluidic channel in its interior-the fundamental mode of vibration only was considered. Due to its importance in practice, we examine the effect of mode number on energy dissipation in these microfluidic beam resonators. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 28 publications
(53 reference statements)
1
35
1
Order By: Relevance
“…In previous studies, energy dissipation has been attributed to environmental factors, such as viscosity, temperature, clamping loss, intrinsic defects, and the change of the elastic energy. 11,15,16,[37][38][39][40][41][42] Here, we take advantage of the in situ technique to directly measure and calculate the input and output energies. The input energy can be assumed as the energy of a capacitor, between the free end of the Si NW and the W probe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, energy dissipation has been attributed to environmental factors, such as viscosity, temperature, clamping loss, intrinsic defects, and the change of the elastic energy. 11,15,16,[37][38][39][40][41][42] Here, we take advantage of the in situ technique to directly measure and calculate the input and output energies. The input energy can be assumed as the energy of a capacitor, between the free end of the Si NW and the W probe.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is still challenging to realize high-order resonances at high frequencies due to the large energy dissipation and strict resonant conditions. 15,16 By using the top-down approach, high-order normal and parametric resonances were demonstrated, 17,18 with a resonant frequency of several MHz. 17 Bottom-up grown nanowires (NWs) are attractive as high frequency resonators because of their high crystallinity and small mass.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, an NSR would have relatively increased sensitivity, by two orders of magnitude, and as a consequence, could detect pressure variations with improved resolution relative to the presented micro-scale prototype. A previous study 25 showed that Q decreases with a decrease in length (mode number) of a resonator. In the case of an NSR, and as evidenced by previous work, an appropriate combination of aspect ratio 26 (Ch w , t, F w , L, Ch h ) could help in retaining high Q.…”
Section: A)mentioning
confidence: 97%
“…Each prong can be individually considered as a clamped-free cantilever beam, and the symmetrical prongs of QTF reduce the number of possible modes. Since the length L of each prong of the tuning fork is much larger than its width l and thickness e, according to the beam theory of Euler-Bernoulli, the governing differential equation for the deflection w(x, t) of the beam [35][36][37] is given by…”
Section: Hydrodynamic Modelmentioning
confidence: 99%